Stability Test For Sorghum Mutant Lines Derived From Induced Mutations with Gamma-Ray Irradiation - S. Human; S. Andreani; Sihono Sihono; W.M. Indriatama (Atom Indonesia, 2011)
Sorghum breeding program had been conducted at the Center for the Application of Isotopes and Radiation Technology, BATAN. Plant genetic variability was increased through induced mutations using gamma-ray irradiation. Through selection process in successive generations, some promising mutant lines had been identified to have good agronomic characteristics with high grain yield. These breeding lines were tested in multi location trials and information of the genotypic stability was obtained to meet the requirements for officially varietal release by the Ministry of Agriculture. A total of 11 sorghum lines and varieties consisting of 8 mutant lines derived from induced mutations (B-100, B-95, B-92, B-83, B-76, B-75, B-69 and Zh-30) and 3 control varieties (Durra, UPCA-S1 and Mandau) were included in the experiment. All materials were grown in 10 agro-ecologically different locations namely Gunungkidul, Bantul, Citayam, Garut, Lampung, Bogor, Anyer, Karawaci, Cianjur and Subang. In each location, the local adaptability test was conducted by randomized block design with 3 replications. Data of grain yield was used for evaluating genotypic stability using AMMI approach. Results revealed that sorghum mutation breeding had generated 3 mutant lines (B-100, B-76 and Zh-30) exhibiting grain yield significantly higher than the control varieties. These mutant lines were genetically stable in all locations so that they would be recommended for official release as new sorghum varieties to the Ministry of Agriculture.Received: 20 November 2010; Revised: 01 August 2011; Accepted: 05 August 2011